Hepatitis C virus NS5A promotes insulin resistance through IRS-1 serine phosphorylation and increased gluconeogenesis - Parvaiz, Fahed (World J Gastroenterol, 2015)
AIM: To investigate the mechanisms of insulin resistance in human hepatoma cells expressing hepatitis C virus (HCV) nonstructural protein 5A (NS5A). METHODS: The human hepatoma cell lines, Huh7 and Huh7.5, were infected with HCV or transiently-transfected with a vector expressing HCV NS5A. The effect of HCV NS5A on the status of the critical players involved in insulin signaling was analyzed using real-time quantitative polymerase chain reaction and Western blot assays. Data were analyzed using Graph Pad Prism version 5.0. RESULTS: To investigate the effect of insulin treatment on the players involved in insulin signaling pathway, we analyzed the status of insulin receptor substrate-1 (IRS-1) phosphorylation in HCV infected cells or Huh7.5 cells transfected with an HCV NS5A expression vector. Our results indicated that there was an increased phosphorylation of IRS-1 (Ser(307)) in HCV infected or NS5A transfected Huh7.5 cells compared to their respective controls. Furthermore, an increased phosphorylation of Akt (Ser(473)) was observed in HCV infected and NS5A transfected cells compared to their mock infected cells. In contrast, we observed decreased phosphorylation of Akt Thr308 phosphorylation in HCV NS5A transfected cells. These results suggest that Huh7.5 cells either infected with HCV or ectopically expressing HCV NS5A alone have the potential to induce insulin resistance by the phosphorylation of IRS-1 at serine residue (Ser(307)) followed by decreased phosphorylation of Akt Thr(308), Fox01 Ser(256) and GSK3β Ser(9), the downstream players of the insulin signaling pathway. Furthermore, increased expression of PECK and glucose-6-phosphatase, the molecules involved in gluconeogenesis, in HCV NS5A transfected cells was observed. CONCLUSION: Taken together, our results suggest the role of HCV NS5A in the induction of insulin resistance by modulating various cellular targets involved in the insulin signaling pathway.